2007
DOI: 10.1074/jbc.m704309200
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like Growth Factor Type-I Receptor Internalization and Recycling Mediate the Sustained Phosphorylation of Akt

Abstract: Previously we demonstrated that insulin-like growth factor-I mediates the sustained phosphorylation of Akt, which is essential for long term survival and protection of glial progenitors from glutamate toxicity. These prosurvival effects correlated with prolonged activation and stability of the insulin-like growth factor type-I receptor. In the present study, we investigated the mechanisms whereby insulin-like growth factor-I signaling, through the insulin-like growth factor type-I receptor, mediates the sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 49 publications
7
86
0
Order By: Relevance
“…Based on evidence for the involvement of GIPC in endocytic trafficking, Wu et al (2006) hypothesized that xGIPC promotes IGF-IR recycling and, consequently, is required for sustained signal transduction and Xenopus eye development. This hypothesis is consistent with our demonstration of sustained PI3-K/Akt signaling in glial progenitors through IGF-IR recycling (Romanelli et al 2007). Although gaps remain in understanding precisely how GIPC regulates RTKs, this receptor-interacting protein has emerged as an interesting target for investigation of RTK trafficking, the regulation of signal transduction and resultant cellular responses.…”
Section: Receptor Interacting Proteinssupporting
confidence: 74%
See 2 more Smart Citations
“…Based on evidence for the involvement of GIPC in endocytic trafficking, Wu et al (2006) hypothesized that xGIPC promotes IGF-IR recycling and, consequently, is required for sustained signal transduction and Xenopus eye development. This hypothesis is consistent with our demonstration of sustained PI3-K/Akt signaling in glial progenitors through IGF-IR recycling (Romanelli et al 2007). Although gaps remain in understanding precisely how GIPC regulates RTKs, this receptor-interacting protein has emerged as an interesting target for investigation of RTK trafficking, the regulation of signal transduction and resultant cellular responses.…”
Section: Receptor Interacting Proteinssupporting
confidence: 74%
“…Moreover, Akt co-localizes with Trk within intracellular membrane fractions in a brain-derived neurotrophic factor (BDNF)-dependent manner in primary neurons (Yano and Chao 2005). Recently, we also demonstrated that IGF-I stimulated Akt phosphorylation requires IGF-IR internalization in glial progenitors (Romanelli et al 2007). These data strongly suggest that endosome-bound receptors are competent for signaling in various cell types and that internalization, in some cases, is required for activated receptors to interact with the appropriate signaling complexes.…”
Section: Rtk Signaling: Plasma Membrane Versus Endosomementioning
confidence: 92%
See 1 more Smart Citation
“…Tyrosine kinase receptors are internalized and degraded on growth factor stimulation. 38,39 Thus, IGF1R protein levels are affected by receptor activation and turnover and do not always reflect receptor expression levels. In addition, immunohistochemistry results can be influenced by a variety of technical factors, including tissue storage and fixation conditions, antigen retrieval protocols, antibody specificity, antibody detection systems, and other methodologic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Mislocalization of IRS-1 reduced IGF-I-dependent tyrosine phosphorylation of IRS-1 and the association with PI 3-kinase without affecting phosphorylation of IGF-IR. Several reports suggest that internalization of IR/IGF-IR is required for proper signal transduction (44)(45)(46)(47). These observations raise the possibility that the IRS-1-IGF-IR association should be spatially restricted in the intracellular membrane compartment, and therefore a defect in AP-1 transport to such compartment could result in reduced tyrosine phosphorylation of IRS-1 by IGF-IR.…”
Section: Discussionmentioning
confidence: 99%